From Classroom to Society: Exploring the Role of Economic Literacy on Public Pedagogy - B. Bamiro, Nurudeen (Asian Journal of Assessment in Teaching and Learning, 2024)
This study delves into the powerful role of economic literacy in sparking public pedagogy and fostering civic engagement. It examines how formal education, innovative teaching strategies, and active public discourse can work together to enhance individuals' economic understanding and participation in society. The study is guided by the PRISMA protocol. The study identified 31 high-quality studies that meet the criteria of relevance, methodological rigor, and recent publication. The study focuses on exploring the role of economic literacy in promoting public pedagogy by addressing three key areas: identifying effective teaching strategies that foster economic literacy, examining classroom environments that extend economic literacy into public pedagogy, and investigating how classroom-based economic literacy programs influence students' engagement in public economic discourse. The review reveals that economic literacy enhances public engagement and drives greater participation in economic matters. Additionally, this research offers a conceptual framework for educators and policymakers, aimed at optimizing the integration of economic literacy into both formal education systems and public pedagogy. These findings shed light on the significant influence of economic education in cultivating informed, engaged, and economically active citizens.